History of biological metal utilization inferred through phylogenomic analysis of protein structures - Dupont, Christopher L. (National Academy of Sciences, 2010)
The fundamental chemistry of trace elements dictates the molecular speciation and reactivity both within cells and the environment at large. Using protein structure and comparative genomics, we elucidate several major influences this chemistry has had upon biology. All of life exhibits the same proteome size-dependent scaling for the number of metal-binding proteins within a proteome. This fundamental evolutionary constant shows that the selection of one element occurs at the exclusion of another, with the eschewal of Fe for Zn and Ca being a defining feature of eukaryotic proteomes. Early life lacked both the structures required to control intracellular metal concentrations and the metal-binding proteins that catalyze electron transport and redox transformations. The development of protein structures for metal homeostasis coincided with the emergence of metal-specific structures, which predominantly bound metals abundant in the Archean ocean. Potentially, this promoted the diversification of emerging lineages of Archaea and Bacteria through the establishment of biogeochemical cycles. In contrast, structures binding Cu and Zn evolved much later, providing further evidence that environmental availability influenced the selection of the elements. The late evolving Zn-binding proteins are fundamental to eukaryotic cellular biology, and Zn bioavailability may have been a limiting factor in eukaryotic evolution. The results presented here provide an evolutionary timeline based on genomic characteristics, and key hypotheses can be tested by alternative geochemical methods.